Efektifitas Pendidikan Kesehatan Tentang Kehamilan Resiko Tinggi Terhadap Pengetahuan Ibu Hamil - Fitriani, Elvi -; Utami, Sri -; HD, Siti Rahmalia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research is to determined the effectiveness of health education about high risk pregnancy for knowledge among pregnant women. The design of this research was Quasy experiment approach with non equivalent control-group were divided into experimental group and control group. The research was conducted in pregnant women in in the “ Puskesmas Rejosari Kecamatan Tenayan Raya. The total sample was 30 people which is the minimum sample that must be fulfilled in quantitative research. Measurement tools use in both of groups was questionaire that had been tested in validity (r = 0,523-0,923) and realibility (r = 0,951). Analysis was used univariate and bivariate analyzes using Dependent test and Independent test. The results showed that there was significant of increase in knowledge of the changes in pregnant woman in the experimental group after the given health education about high-risk pregnancy with p value (0.000) < α (0,05). It means that health education about high-risk pregnancy effective to improve the knowledge pregnant woman. It is recommended for health provider especially mother and children health unit to always give health education about high-risk pregnancy. Keywords : High-risk pregnancies, knowledge, health education.